Effect of Massage Therapy on Hyperbilirubinemia among Neonates Suffering From Neonatal Jaundice: A Randomized Controlled Trial - Rimple Pathania; Bharat Pareek; Rajesh Shyoran; Sain Priya; Ramya Kundayi Ravi; Salizar Mohamed Ludin (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: Neonatal jaundice is a common condition that requires medical attention in newborns. Although phototherapy is considered the first option to treat hyperbilirubinemia in neonates, massage therapy is considered a safer, more affordable, culturally acceptable, and effective alternative to phototherapy in many parts of the world. This study aimed to evaluate the effectiveness of massage therapy for hyperbilirubinemia in neonates with neonatal jaundice. Methods: A hospital-based, parallel-group, randomized controlled trial was conducted to assess the effectiveness of massage therapy on bilirubin levels in neonates. The neonates were randomly assigned using simple random allocation using sealed opaque envelopes to either an experimental group (n = 35), which received massage therapy twice daily for three consecutive days, or a control group (n = 35), which received standard treatment. However, only 30 participants in each group completed the study; therefore, a total of 60 participants were included in the final analysis. Blinding was not feasible for participants and care providers; however, outcome assessment was performed by a blinded assessor. The effectiveness of the intervention was evaluated with a significance level of ? ? 0.05, and the primary outcome was measured by bilirubin levels on the third day post-intervention. Results: Although there were no significant differences in the mean ± SD score of serum bilirubin level on day one (p = 0.503) and day two (p = 0.472), a statistically significant difference (p = 0 .023) was observed on day three (Experimental group = 8.01 ± 1.93, control group = 9.15 ± 1.85) of intervention. Conclusion: Massage therapy has been shown to be an effective intervention for lowering bilirubin levels in neonates. This study recommends massage therapy as an adjunct treatment for neonatal hyperbilirubinemia.